2015
DOI: 10.1016/s0924-9338(15)31186-x
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine in the Treatment of Children with PTSD

Abstract: Introduction: Military action in Ukraine led to increasing in the number of patients with PTSD among children. Open-label studies demonstrated the efficacy of SSRI's for the treatment of PTSD, primarily paroxetine. Feasibility of using of these drugs in children and adolescents is controversial [1-2]. Objective: To evaluate a short and long-term efficacy and tolerability of fluoxetine in the treatment of PTSD in children. Methods: double-blind, placebo-controlled 12-week study with a fixed dose of fluoxetine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The exact underlying mechanism of the development of PTSD following trauma yet remains to be fully understood. However, disruption of the autonomic nervous system and sympathetic response secondary to alterations in basal NE level, along with the excessive release of NE and symptoms related to this hyper-noradrenergic state following a traumatic event or its reminders, have been shown to play a role in the pathophysiology of PTSD [ 51 , 52 ]. Psychoneurological evaluation of trauma victims and neuroimaging evidence have shown associations with the structure and functioning of the brain and PTSD, especially the dysfunction of the cortical regions associated with working memory and sympathetic fight-and-flight response, including the amygdala and PFC, in response to life-threatening cues [ 13 , 53 , 54 ].…”
Section: Reviewmentioning
confidence: 99%
“…The exact underlying mechanism of the development of PTSD following trauma yet remains to be fully understood. However, disruption of the autonomic nervous system and sympathetic response secondary to alterations in basal NE level, along with the excessive release of NE and symptoms related to this hyper-noradrenergic state following a traumatic event or its reminders, have been shown to play a role in the pathophysiology of PTSD [ 51 , 52 ]. Psychoneurological evaluation of trauma victims and neuroimaging evidence have shown associations with the structure and functioning of the brain and PTSD, especially the dysfunction of the cortical regions associated with working memory and sympathetic fight-and-flight response, including the amygdala and PFC, in response to life-threatening cues [ 13 , 53 , 54 ].…”
Section: Reviewmentioning
confidence: 99%
“…Більшість досліджень ефективності ПЛЗ у дітей та підлітків після травматизації мали на меті оцінювання їх ефективності при лікуванні симптомів ПТСР [57]. Окремі дослідження вказують на безпечність та ефективність флуоксетину при терапії депресивних симптомів при ПТСР у дітей та підлітків, які зазнали травматизації під час воєнних дій [46,47].…”
Section: терапіяunclassified
“…Only a few studies have prospectively and systematically evaluated the use of pharmacological agents in youth with PTSD. One open-label study with citalopram ( 12 ) and one double-blind, placebo-controlled 12-week study with a fixed dose of fluoxetine ( 13 ) demonstrated improved symptoms over the course of treatment; however, randomized controlled trials of antidepressants, both tricyclic and serotoninergic, have not shown benefit ( 14 16 ). Similarly, second-generation antipsychotics (SGA) may be associated with improvement in some PTSD symptoms, but these results are supported by very few pharmacological studies, limited to case series ( 17 , 18 ) and open-label studies for risperidone ( 19 ) and quetiapine ( 20 ).…”
Section: Introductionmentioning
confidence: 99%